Rotary Motion and Manipulation Using Electro-Hydraulic Actuator With Asymmetric Electrodes - Kim, Sohyun; Cha, Youngsu (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
Soft robotics require unique and novel actuators for various applications. Therefore, a novel soft electro-hydraulic actuator is proposed and its ability to manipulate a spherical object on an active plate is demonstrated. The proposed actuator has two actuation parts with asymmetric electrodes. Two types of deformations are created by applying voltages to the asymmetric electrodes of the actuator. By using various deformations from four electro-hydraulic actuators, an active plate is realized. The active plate can exhibit eight different inclinations that, allow a ball to be stopped in a desired target location. The results demonstrate that the ball's movement in a circular path may be maintained using active plate. Further, the ball can stop at the desired target points.
Keywords: DIELECTRIC ELASTOMERS; SOFT ROBOTICS